Tocilizumab for refractory systemic juvenile idiopathic arthritis - Lai, J M (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2017)
Objective: To evaluate the efficacy and side effects of tocilizumab for the treatment of systemic juvenile idiopathic arthritis. Method: In this prospective self case-control study, the children diagnosed with refractory systemic juvenile idiopathic arthritis admitted to Department of Rheumatism and Immunology of Children's Hospital Affiliated to Capital Institute of Pediatrics from December 2013 to June 2016 were enrolled and information before and after treatment of tocilizumab was analyzed. The tocilizumab was introvenously guttae in a dose of 8-12 mg/kg every 2 weeks. Complete blood count, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were tested before and after the application of tocilizumab. Detailed clinical manifestations were recorded. All results were analyzed by χ(2) test and t test. Result: Forty patients with a median age of (6.6±3.7) years were enrolled, including 15 males and 25 females. All of the patients presented with fever and 38 patients got normal temperature 24-48 hours after treatment with tocilizumab. Symptoms disappeared in 13 and improved in 4 patients after treatment among the 17 patients who presented with arthritis. Within the 10 patients who manifested with rashes, 9 patients' rashes disappeared without relapse accompanied by the normalization of temperature after the treatment of tocilizumab. One patient got normal temperature but intermittently emerged rashes after symptoms of arthritis improved. In the 40 patients, 38 well tolerated tocilizumab while 2 showed rashes and chill which disappeared shortly after antianaphylaxis treatment. No severe treatment-related infection was found in any patients. According to the study, the white blood cell counts(×10(9)/L), CRP(mg/L) and ESR(mm/1h) tested 2 weeks after the treatment with tocilizumab were significantly lower than that before treatment(12.1±1.2 vs. 16.5±1.8, 47±8 vs. 67±9, 21±5 vs. 57±6, t=2.75, 3.98, 5.22, P=0.009, 0, 0, respectively). No significant changes were found in concentration of IL-6 and TNF-α (65(207) vs. 45(137) ng/L, and 14(6) vs. 17(19)ng/L, Z=-1.247 and-1.285, P=0.212 and 0.199 respectively). Conclusion: Tocilizumab is a treatment with good efficacy and safety for refractory systemic juvenile idiopathic arthritis. Adverse effects would be found in some patients